CURING HYPERTENSION: SUCCESFUL ADRENALECTOMY FOR PRIMARY ALDOSTERONISM USING CONTRALATERAL SUPPRESSION INDEX - Amin, Md S Md; Ibrahim, L; Vethakkan, S R (Journal of the ASEAN Federation of Endocrine Societies, 2021)
INTRODUCTION The diagnosis of Primary Aldosteronism can be challenging especially when it comes to localising an adenoma in patients who fail adrenal venous sampling. Even in expert hands, the right adrenal vein has been known to be difficult to cannulate during AVS. We present a case of a hypertensive woman with metabolic alkalosis and hypokalemia who was evaluated for primary hyperaldosteronism. RESULTS A 57-year-old Chinese female with a history of mini-gastric bypass with resultant resolved DM, attended clinic for poorly-controlled hypertension on 2 anti- hypertensives. She also had persistent hypokalemia (2.9-3.5 mmol/l) with metabolic alkalosis. She denied paroxysms or abnormal weight gain suggestive of phaeochromocytoma or Cushing’s syndrome. Physical examination was unremarkable. Her aldosterone-renin-ratio (ARR) was raised (>91) with a serum aldosterone of 747 pmol/L and renin of <1.8mU/L. A saline suppression test showed a non-suppressed aldosterone (767pmol/L). A CT-adrenal 3-phase confirmed a subcentimeter benign right adrenal gland nodule with an absolute washout of 92%, suggestive of Conn’s adenoma. 24-hour urine catecholamines/metanephrines and 24-hour urinary cortisol were negative. She underwent adrenalvein-sampling (AVS) with cosyntropin stimulation to localise the source of excess aldosterone secretion. Three series of cortisol samples demonstrated selectivity indices between 0.9-1 for the right and 6.4-24.4 for the left adrenal veins, reflecting failed right adrenal vein cannulation. Contralateral suppression index (CSI) was <1 for all 3 samples from the left adrenal vein. She was referred to the surgeons for right retroperitoneal adrenalectomy. Histopathology confirmed a 1 x 1 cm adrenal cortical adenoma. She was able to cease all anti-hypertensives and potassium supplementation immediately after the surgery. CONCLUSION Studies have shown that CSI has a positive predictive value up to 88.9%. Use of CSI in this patient was helpful in demonstrating absolute suppression of the contralateral zona glomerulosa of a normal adrenal gland, thus lateralising the culprit adenoma and curing a patient of hypertension.